Assistance in Determining the Cost of Goods Sold (COGS) at UMKM Nadira Villa Cake, Sungai Penuh City - Carolina, Cyntia (The Future of Education Journal, 2024)
The Assistance Program for Determining the Price of Goods Sold at Nadira Villa Cake MSMEs in Sungai Penuh is held in order to support the development of MSMEs in Sungai Penuh, activities can be organized well and run smoothly in accordance with the activity plans that have been prepared. This activity received a good response from business actors and owners of Nadira Villa Cake. From this Community Service activity, Business Owners have received training in determining the cost of goods sold as a basis for determining the selling price and expected profit level. The importance of recording every transaction in terms of Raw Materials, Labor and Factory Overhead is the basis for determining the level of profit and selling price. This activity was carried out as support for the local potential development program in an effort to increase the income of MSMEs in Sungai Penuh City.